A study of storage impact on ovalbumin structure of chicken egg. (February 2018) - Sheng, Long; Huang, Mengjie; Wang, Jing; Xu, Qi; Hammad, H.H.M.; Ma, Meihu
Abstract: During the egg storage, the change in structure of ovalbumin (OVA) was determined by spectroscopy of Fluorescence, Circular Dichroism and Fourier-Transform Raman. The relationships between the OVA properties and structure were also investigated in this study. Comparing with the consequence of Circular Dichroism and Fourier-Transform Raman spectra, it was obvious that the percentage of α-helix and β-sheet showed downward trends after storage. In contrast, the percentage of β-turn and random coil clearly presented raising trend. Furthermore, tryptophan residues were buried in a more hydrophobic environment. The emulsifying and foaming properties of OVA all decreased during the storage. Moreover, the correlation analysis indicated that β-sheet related to the emulsifying stability of OVA ( p < 0.01), α-helix related to the foaming stability ( p < 0.05) at the same time. This study provided new interesting idea for the study on the relationships between the structure and functional properties of protein during food storage. Graphical abstract: Highlights: OVA content declined when eggs were stored at 22 °C and 65% relative humidity. Percent of α-helix & β-sheet of OVA declined, percent of β-turn & random coil rose. Emulsifying & foaming properties of OVA all decreased during the storage. Emulsifying & foaming properties of OVA were related with protein structure.